Genetic characterization of influenza B virus in Cameroon and high frequency of reassortant strains. Issue 12 (27th August 2018) - Monamele, Chavely Gwladys; Vernet, Marie‐Astrid; Njankouo, Mohamadou Ripa; Kenmoe, Sebastien; Schoenhals, Matthieu; Yahaya, Ali Ahmed; Anong, Damian Nota; Akoachere, Jane Francis; Njouom, Richard
Abstract: Influenza B is broadly divided into B/Victoria and B/Yamagata lineages based on its genetic and antigenic properties. We describe in this study the first report on genome characterization of type B influenza virus in the Cameroon National Influenza Center (NIC) between 2014 and 2017. Respiratory samples were collected as part of the influenza surveillance activity in the NIC. RNA products were tested for the presence of influenza using the CDC Influenza A/B typing panel. Thirty‐five samples positive for influenza B were selected for sequencing three gene segments (HA, NA, and M) and phylogenetic trees were generated by MEGA version 6.0. Nucleotide phylogenetic analysis of the HA gene revealed the presence of three major clades among Cameroonian strains. All Victoria lineages grouped into B/Victoria clade 1A, while, Yamagata lineages grouped into Yamagata clade 2 (2014 strains) and Yamagata clade 3 (2015‐2017). We observed a high frequency of reassortant viruses with Yamagata‐like HA gene and Victoria‐like NA gene (27.4%; 23/84). The results from this study confirm variations in the genome composition of type B influenza virus and emphasize on the relevance of molecular surveillance for spotting peculiar genetic variants of public health and clinical significance.